Modified Computed Tomography Scoring System for Ovarian Tumors - Areepongsa, Onnicha; Cattapan, Kamonwon; Leelakiatpaiboon, Siriporn; Tubtawee, Teeravut; Jiamset, Ingporn (Journal of Health Science and Medical Research, 2024)
Objective: Ovarian cancer is the sixth most common cancer in Thailand. Given the absence of a computed tomography (CT) score for differentiating between benign and malignant ovarian tumors, this study aimed to develop a CT scoring system for differentiating between benign and malignant ovarian tumors using pathologic findings as the reference standard. Material and Methods: This retrospective study included all female patients having undergone abdominal/pelvic CT scans for evaluation of ovarian masses at our institute, from January 2011 to December 2021. Two radiologists independently reviewed CT features and obtained a CT score for each tumor. Comparison of the differentiation performance of the CT score, with reference to the pathologic findings, was performed using Fisher’s exact or chi-squared test. The diagnostic performance of the CT score was evaluated. Results: A total of 144 patients with 191 ovarian masses were enrolled. Tumor component characteristics, septate thickness, ascites, and metastasis significantly differed between benign and malignant tumors (p-value<0.05). Multivariate logistic regression analysis showed that the presence of solid components and metastasis were significant independent differentiating factors (p-value<0.001). The CT score significantly differed between benign and malignant tumors (p-value<0.001), with 93.5% sensitivity and 81.6% specificity. Conclusion: The CT scoring system can differentiate between benign and malignant ovarian tumors with high sensitivity and specificity. Furthermore, the presence of a solid component and metastasis are CT features that can be used to differentiate between benign and malignant tumors.